The Effectiveness of Logotherapy in Enhancing Meaning in Life Among Individuals with Depressive Disorders: A Systematic Literature Review - Dhiya’ Almirra Azzahra; M. Suharsono (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Depressive disorder is a mental health condition commonly characterized by feelings of emptiness, loss of interest, decreased energy, and reduced motivation, reflecting a crisis of life meaning. Depression, beyond affective and somatic symptoms, is intrinsically associated with feelings of emptiness and a loss of life purpose. Logotherapy, developed by Viktor Frankl, emphasizes the search for meaning in life, known as the will to meaning, as the primary motivational force in humans, and posits that suffering can be transformed when individuals find meaning within it. The research method used a systematic literature review with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search was conducted through Google Scholar, PubMed, and Crossref databases using the keywords